Horticultural performance of ‘Fuji Suprema’ and ‘Maxi Gala’ apple trees trained at Tall Spindle and Bi-Axis systems grafted on different rootstocks in Southern Brazil - Rufato,Leo (2022)
ABSTRACT: The use of new rootstocks combined with different training systems have been studied to increase productivity, fruit quality, and reduce costs. Another important factor is the validation of studies under replanting conditions, due to the growing limitation of new areas for planting commercial apple orchards in Brazil. The present study aimed to evaluate the behavior of ‘Fuji Suprema’ and ‘Maxi Gala’ apple trees in two training systems grafted on two rootstocks. The study occurred during the seasons 2016/17, 2017/18 and 2018/19, in an orchard located in southern Brazil in an area previously cultivated with apple trees. A randomized block design consisting of a 2x2 factorial was used, with Tall Spindle and Bi-Axis as the training system and ‘M.9’ and ‘G.213’ as rootstocks of Fuji Suprema and Maxi Gala cultivars. Variables were evaluated to determine tree vigor, as well as yield and fruit quality characteristics. It was observed that ‘G.213’ promoted higher vigor for both cultivars as well as the Bi-Axis training system in the Maxi Gala cultivar. The highest yield was observed in Tall Spindle as well as the rootstock ‘G.213’ in both cultivars. The most significant changes on fruit quality occurred in the Bi-Axis training system, presenting higher intensity of red color as well as ‘Maxi Gala’ grafted on ‘G.213’ rootstock.